2023
DOI: 10.1038/s41467-023-38215-z
|View full text |Cite|
|
Sign up to set email alerts
|

A pesticide and iPSC dopaminergic neuron screen identifies and classifies Parkinson-relevant pesticides

Abstract: Parkinson’s disease (PD) is a complex neurodegenerative disease with etiology rooted in genetic vulnerability and environmental factors. Here we combine quantitative epidemiologic study of pesticide exposures and PD with toxicity screening in dopaminergic neurons derived from PD patient induced pluripotent stem cells (iPSCs) to identify Parkinson’s-relevant pesticides. Agricultural records enable investigation of 288 specific pesticides and PD risk in a comprehensive, pesticide-wide association study. We assoc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 57 publications
0
22
0
Order By: Relevance
“…In the specific context of pesticides, impacts of common genetic variation ( GSTP1 , ABCB1 ) and PD-associated mutations ( LRRK2 G2019S) on response to herbicide, organochlorine, and paraquat exposure have been identified in both human and model organism studies 77 80 . While we identified different SNPs associated with pesticide exposure in this study, it is still possible they may have influenced response to exposure, which could be resolved with more precise accounting of exposure and supported by experimental studies 73 . On the whole, the lack of association between SNPs explaining DNAm at PD-associated CMRs in TERRE and SNPs associated with genetic risk for PD in populations of European ancestry suggested that SNP genotype may impact DNAm levels at the given CMRs independently of PD status (for instance, if PD cases and controls had different genotypes by chance), and/or that genotype and PD could both be associated with additional unmeasured factors, such as population-specific G × G or G × E interactions 29 , 76 .…”
Section: Discussionmentioning
confidence: 76%
“…In the specific context of pesticides, impacts of common genetic variation ( GSTP1 , ABCB1 ) and PD-associated mutations ( LRRK2 G2019S) on response to herbicide, organochlorine, and paraquat exposure have been identified in both human and model organism studies 77 80 . While we identified different SNPs associated with pesticide exposure in this study, it is still possible they may have influenced response to exposure, which could be resolved with more precise accounting of exposure and supported by experimental studies 73 . On the whole, the lack of association between SNPs explaining DNAm at PD-associated CMRs in TERRE and SNPs associated with genetic risk for PD in populations of European ancestry suggested that SNP genotype may impact DNAm levels at the given CMRs independently of PD status (for instance, if PD cases and controls had different genotypes by chance), and/or that genotype and PD could both be associated with additional unmeasured factors, such as population-specific G × G or G × E interactions 29 , 76 .…”
Section: Discussionmentioning
confidence: 76%
“…Due to cumulative or possibly even synergistic effects, such cocktails may contribute to a much higher risk of developing PD. A recent study in California suggests that co-exposure to multiple pesticides is associated with much greater damage to dopaminergic neurons than exposure to any single compound [ 62 ], yet current regulatory actions only consider the neurotoxicity of isolated compounds.…”
Section: The Principal Causes Of Parkinson’s Diseasementioning
confidence: 99%
“…Most presently known PD linked pesticides have been banned in many areas of the world, particularly in high income regions, yet some of these pesticides continue to be used in SSA. Table 1 also shows organochlorines linked to PD [ 5, 25 ] which have been banned in many countries including SSA but still being used in the United States. Despite documented adverse effects on the ecosystem and carcinogenic risks, hazardous pesticides persist in SSA for lack of affordable and safer alternatives to control famine and epidemics.…”
Section: A Global Reservoirmentioning
confidence: 99%